3‐D shear wave velocity structure in the shallow crust of the Tan‐Lu fault zone in Lujiang, Anhui, and adjacent areas, and its tectonic implications. Issue 3 (8th June 2020) - Li, Cheng; Yao, HuaJian; Yang, Yuan; Luo, Song; Wang, KangDong; Wan, KeSong; Wen, Jian; Liu, Bin
Abstract : The Tan‐Lu fault zone is a large NNE‐trending fault zone in eastern China. Investigations of the structures of the fault zone and its surrounding areas have attracted much attention. In this study, we used dense‐array ambient noise tomography to construct a three‐dimensional shear wave velocity model of shallow crust in an area about 80km × 70km in Lujiang, Anhui Province, eastern China. For approximately one month we collected continuous ambient noise signals recorded by 90 short‐period seismographs in the region, and obtained the short‐period Rayleigh wave empirical Green's functions between stations by the cross‐correlation method; we also extracted 0.5–8 s fundamental mode Rayleigh wave group velocity and phase velocity dispersion curves. Based on the direct surface wave tomography method, we jointly inverted the group velocity and phase velocity dispersion data of all paths and obtained the 3‐D shear wave velocity structure in the depth range of 0–5 km. The results revealed important geological structural features of the study area. In the north region, the sedimentary center of the Hefei Basin — the southwestern part of the Chaohu Lake — shows a significant low‐velocity anomaly to a depth of at least 5 km. The southwestern and southeastern regions of the array are the eastern margin of the Dabie orogenic belt and the intrusion area of Luzong volcanic rocks, respectively, and both show obvious high‐speed anomalies; the sedimentary area within the Tan‐Lu fault zone (about 10 km wide) shows low‐velocity anomalies. However, the volcanic rock intrusion area in the fault zone is shown as high velocity. Our shallow crustal imaging results reflect the characteristics of different structures in the study area, especially the high‐speed intrusive rocks in the Tan‐Lu fault zone, which were probably partially derived from the magmatic activity of Luzong volcanic basin. From the Late Cretaceous to Early Tertiary, the Tan‐Lu fault zone was in a period of extensional activity; the special stress environment and the fractured fault zone morphology provided conditions for magma in the Luzong volcanic basin to intrude into the Tan‐Lu fault zone in the west. Our 3‐D model can also provide important information for deep resource exploration and earthquake strong ground motion simulation.